Efficacy and safety of nivolumab in bone metastases from renal cell carcinoma: Results of the GETUG-AFU26-NIVOREN multicentre phase II study. (March 2023) - Velev, Maud; Dalban, Cécile; Chevreau, Christine; Gravis, Gwenaelle; Negrier, Sylvie; Laguerre, Brigitte; Gross-Goupil, Marine; Ladoire, Sylvain; Borchiellini, Delphine; Geoffrois, Lionnel; Joly, Florence; Priou, Frank; et al.
Abstract: Introduction: Bone metastases (BM) in renal cell carcinoma (RCC) are associated with a poor prognosis based on retrospective studies evaluating antiangiogenic agents. Few data are available regarding immune checkpoint inhibitors (ICI) in patients with bone metastatic RCC. NIVOREN is a multicentre prospective study in which patients were treated with nivolumab after the failure of antiangiogenic agents. We aim to assess the impact of BM on prognosis, and the efficacy and safety of nivolumab in patients enrolled in the NIVOREN trial. Materials and methods: All patients with BM at inclusion were included in our study. The primary endpoint was overall survival (OS). Secondary endpoints were progression-free survival (PFS), objective response rate (ORR), safety, and skeletal-related events (SRE). Results: Among 720 patients treated with nivolumab, 194 presented BM at inclusion. The median follow-up was 23.9 months. Median OS was 17.9 months in patients with BM versus 26.1 months in patients without BM (p = 0.0023). The difference was not statistically significant after adjustment (p = 0.0707). The median PFS was shorter in patients with BM even after adjustment (2.8 versus 4.6 months, p = 0.0045), as well as the ORR (14.8% versus 23.3%). SRE occurred for 36% of patients with BM. A post-hoc analysis evaluating the impact of bone-targeting agents (BTA) on SRE incidence showed a significant benefit of BTA on the incidence of SRE (OR = 0.367, CI95% [0.151–0.895]). Conclusion: Nivolumab is associated with shorter PFS, and lower ORR in RCC patients with BM. Our study suggests that BTA in association with immunotherapy decreases the incidence of SRE. Highlights: Lower efficacy of nivolumab if bone metastases (BM) in renal cell carcinoma (RCC). Negative impact of BM, known with antiangiogenic agents, still present with nivolumab. First study evaluating bone-targeting agents (BTA) with immunotherapy in RCC with BM. Benefit of BTA on skeletal-related events incidence without an increase of BTA toxicity. The use of BTA with immunotherapy alone should be considered.